The influence mechanism of upward social comparison on work withdrawal behavior of rural-origin civil servants: based on the mediating effect of ego depletion and the moderating effect of social mobility belief - Zhang, Jingyuan; Yan, Fengjuan; Meng, Lin (Frontiers in Psychology, 2025)
As the sustained popularity of civil service careers persists, a significant number of young people from rural backgrounds have entered the civil service. However, due to differences in social status and background, rural-origin civil servants are prone to engaging in upward social comparison. This results in ego depletion and subsequently induces work withdrawal behavior, adversely affecting team harmony and sustainable development. This study empirically examines the mechanism by which upward social comparison influences work withdrawal behavior among rural-origin civil servants. The concepts of ego depletion and social mobility belief are introduced, with ego depletion further categorized into three dimensions: cognitive, emotional, and behavioral dimensions. Analysis of questionnaire data collected from 1,137 rural-origin civil servants in Jinan, Shandong Province, yielded the following findings: Upward social comparison significantly predicted work withdrawal behavior. Cognitive and emotional ego depletion positively mediated the relationship between upward social comparison and work withdrawal behavior. Furthermore, the mediating effect of emotional ego depletion was stronger than that of cognitive ego depletion. Social mobility belief negatively moderated the pathways through which upward social comparison influences cognitive ego depletion, behavioral ego depletion, and work withdrawal behavior. This research offers a new perspective for understanding the psychological mechanisms underlying work withdrawal behavior among rural-origin civil servants and provides a theoretical basis for targeted interventions.